New Strategies for Historical Towns in the South of Italy. Rethinking Values, Physical Constraints, and Technological opportunities - Antonella Mamì (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
The hinterland of central and southern Italy and the Islands is interspersed with mostly neglected architectural and urban heritage. These territories present many infrastructural, orographic, and economic constraints. A survival economy had survived, strongly tied to their productive, physical, and cultural identity. New models of the economy (sustainable, responsible, circular, green, sharing, and low-cost models) and new instances in the field of architecture and urban planning (accessible and inclusive spaces built for people) are certainly more appropriate for the reinterpretation of towns with a strong historical connotation: their characteristics are closer to a culture of quality, identity, slowness, without renouncing centrality, something that digital and internet connections allow despite the physical distance. A careful study of these places shows the recurrence of considerable constraints that can no longer be considered impossible. New technologies (digital, domotic, wireless, urban vehicle concepts, etc.) and the 4.0 revolution in the industrial field, which implies the use of enabling technologies, none of which requires physical proximity, support us in the study of specific compatible solutions for the reuse of urban and building heritage.